2,7-Bis(2,6-diisopropylphenyl)benzo[lmn][3,8]phenanthroline-1,3,6,8( 2H, 7H)-tetraone - Wu, Xiang-Xiang; Zhang, Shu-Ling; Ng, Seik Weng (International Union of Crystallography, 2010)
In the title compound, C(38)H(38)N(2)O(4), the 16 atoms comprising the four six- membered rings that are fused together are approximately coplanar (maximum r.m.s. deviation = 0.033 angstrom). The benzene rings at either ends are nearly perpendicular to the mean plane of the fused- ring system; one is aligned at 80.4 (1)degrees and the other at 82.2 (1)degrees